Oxford textbook of respiratory critical care - Singh, Suveer; Pelosi, P.; Morris, Andrew Conway (Oxford : Oxford University Press, 2023)
Respiratory critical care is essential to modern critical care medicine. To successfully support critically ill patients, an understanding of specific lung conditions and syndromes, their pathophysiological basis, and evidence-based management strategies is of vital importance. This textbook provides an authoritative account of respiratory critical care medicine with a clear focus on how to manage respiratory disease in the critically ill. The fundamentals of pathophysiology, diagnosis, and treatment, for respiratory diseases and conditions are outlined with a specific focus on management in the critical care setting.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on August 21, 2023).
Keywords: Respiratory intensive care; Health and Wellbeing; Clinical & internal medicine